День счастья - завтра: роман / Оксана Робски - Робски Оксана (АСТ, 2010)
Экземпляры: АБ (20110622) / Инвентарный номер: 39710zzzzz / Цена: 234.33 / Сис.шифр: 84(2) / Авт.знак: Р 58 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)